Breastfeeding, Personal Responsibility and Financial Incentives. (2nd August 2021) - Hoskins, Katelin; Schmidt, Harald
Abstract: Should financial incentives be offered to mothers for breastfeeding? Given the significant socioeconomic and sociodemographic differences in breastfeeding in the USA, researchers and policymakers are exploring the role of financial incentives for breastfeeding promotion with the objective of increasing uptake and reducing disparities. Despite positive outcomes in other health domains, the acceptability of financial incentives is mixed. Financial incentives in the context of infant feeding are particularly controversial given the complex obligations that characterize decisions to breastfeed. After situating the specific ethical tensions related to personal responsibility, fairness, and intrusiveness, we argue that exploring carefully designed financial incentives can be ethically justified to support breastfeeding uptake particularly given (i) established medical guidelines that support breastfeeding benefits, (ii) wide socioeconomic and racial/ethnic disparities and (iii) notable influences in the broader choice architecture of infant feeding in the USA. Additional empirical research is warranted to better understand effectiveness, cost and specific ethical concerns related to free and informed choice.